The Mousterian Settlement in the Ciota Ciara Cave: the oldest evidence of Homo Neanderthalensis in Piedmont (Northern Italy) (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2012)
-
Keywords: Mousterian; Piedmont; lithic technology; paleo-environment; supply areas